2013
DOI: 10.2519/jospt.2013.4830
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Physical, and Neurophysiological Impairments Associated With Decreased Function in Women With Carpal Tunnel Syndrome

Abstract: [ research report ] C arpal tunnel syndrome (CTS) is a disorder characterized by compres sion of the median nerve at the carpal tunnel, often as a result of repetitive activities. 40The clinical presentation of CTS includes motor and sensory deficits in the median nerve distribution and numbness, which may be worse during the night. 31 Women are most often afflicted with CTS, with a reported annual incidence of 139 per 100 000 females, compared to 67 cases per 100 000 males.6 CTS can result in considerable pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A potential association between the intensity of pain and self‐reported function in patients with neuropathic pain was previously reported by Seventer et al . Therefore, it seems clear that nociceptive pain has an effect on function in individuals with chronic pain including CTS . Some studies showed that the intensity of pain was a predictor of worse function in a variety of pain conditions, including low back pain or sciatica .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A potential association between the intensity of pain and self‐reported function in patients with neuropathic pain was previously reported by Seventer et al . Therefore, it seems clear that nociceptive pain has an effect on function in individuals with chronic pain including CTS . Some studies showed that the intensity of pain was a predictor of worse function in a variety of pain conditions, including low back pain or sciatica .…”
Section: Discussionmentioning
confidence: 75%
“…Nunez et al observed that two psychological variables, that is, misinterpretation of nociception and depression, were associated with the intensity of pain in different hand pain conditions, including CTS . Another study reported that the intensity of pain and depression were associated with hand function in women with CTS . These studies would support a potential relationship between the intensity of hand pain, function and depression, among other variables; however, all these studies included an analysis without considering potential direct and indirect interactions between these variables.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the women were at the age of menopause. Fernández-de-Las-Peñas C et al found that a number of factors were associated with function in women with CTS 10 ) . The effect of female psychology on the progress of healing after carpal tunnel surgery should be examined in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Women are reported to be more at risk of CTS than men, probably due to their culturally mandated gender-related duties at home. Hormonal changes that occur at menopause may also be associated with CTS 4 , 9 , 10 ) . Other factors associated with a poor prognosis following surgery are older age, an extended history of CTS, and prolonged or absent sensation or motor response 2 , 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported associations between pain intensity and function with psychological (e.g., depressive levels), psychophysical (i.e., pressure pain sensitivity), and physical (lower pinch tip grip force) outcomes in a sample of women with CTS [8][9][10]. Previous studies used linear regression analyses to determine the associations between the dependent variable(s) and independent variables.…”
Section: Introductionmentioning
confidence: 99%